39 Virtual Clinics in Foot & Ankle Surgery: Patient and Clinician Perceptions and Review of The Literature. (12th October 2021) - Rhind, J H; Devany, A; Ramhamadany, E; Ismael, S; Heaver, C; Hill, S
Abstract: Aim: The COVID 19 worldwide pandemic has led to the popularisation of, "Virtual" clinics. Within orthopaedics, little is known about the use of virtual clinics within foot and ankle surgery, specifically. Method: A cross sectional observation study of patients and clinicians in response to virtual clinics in foot and ankle surgery. Patients seen in a virtual clinic were contacted from two weeks after their consultation by telephone with a 12-point questionnaire. Demographic information was also collected. Clinicians in foot and ankle also completed a 10-point questionnaire. Results: 100 patient responses were collected. Patient satisfaction with virtual clinics was positive, 65% were very happy (Likert scale rating 5). >90% of patients felt they received enough information, felt involved, felt it was helpful and knew who to contact if there was a problem. However, 79% would still prefer a face-to-face consultation. 22% would have preferred a video consultation. Clinician responses were more cautious, 60% were neither happy nor unhappy (Likert scale rating 3). Virtual clinics may be faster for the clinician. Conclusions: Virtual clinics may be more convenient for patients with high satisfaction levels but represent significant clinical challenges for foot and ankle surgeons. Elements of virtual clinics may persist post pandemic, particularly in routine follow up patients. Virtual clinics are not appropriate for new patient referrals.